Implementasi Perda Kabupaten Kutai Kartanegara No.23 Tahun 2016 Tentang Pencegahan Dan Penanggulangan Praktek Seks Komersial (Studi Kasus Warung Kopi Pangku Desa Bukit Raya Kabupaten Kutai Kartanegara) - Aulia Mardiana; Jumansyah, Jumansyah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
The purpose of the research is to analyze and describe the Implementation of Kutai Kartanegara Regency Regional Regulation No.23 of 2016 concerning Prevention and Control of Commercial Sex Practices in Warung Kopi Pangku Area, Bukit Raya Village, Kutai Kartanegara Regency. The method used in the research is descriptive qualitative with primary data sources conducted by means of observation, interviews and documentation and secondary data sources obtained from journals, articles and others related to the research conducted. The results showed that the Implementation of Kukar Regional Regulation No.23 of 2016 concerning Prevention and Control in the Pangku Coffee Shop Area, Bukit Raya Village, Kukar Regency has not been fully implemented by the Kukar Social Service and Kukar Satpol PP, until now the practice of prostitution in the pangku coffee shop area still continues to occur. Of the total 6 indicators in the prevention and control listed in the Regional Regulation, only 2 have been implemented. This happens because there are still some obstacles and constraints in implementing the regulation. One of the obstacles in the implementation of the local regulation is the unclear content of the local regulation, because the local regulation does not mention clearly and in detail about who are the authorized parties in the local regulation, resulting in confusion of policy implementers in taking steps.